X-ray Photoelectron Spectroscopy Reveals the Chemical Composition of Antimicrobial Self-Assembled Thin Films Containing the LL-37 Peptide - Vranckx, Cédric; de Wilmars, Alix Mertens; Eloy, Pierre; Cornu, Olivier; Dupont-Gillain, Christine (Applied surface science, 2025)
[Display omitted] •XPS is a key tool to study the relative composition of nanofilms with biomolecules.•XPS affects nitrogen group protonation, with empirical α lower than theoretical.•LL-37 proportion is lower in PPCsLL-37-Hep multilayers than in bare LL-37 ones. The surface immobilization of LL-37, a cationic antimicrobial peptide, offers a promising route for developing antibacterial coatings. In this study, two different strategies were used to immobilize LL-37: (i) bare LL-37 molecules were directly assembled layer-by-layer (LbL) with negatively-charged heparin (Hep), and (ii) LL-37 was first complexed with Hep, forming peptide-polyelectrolyte complexes (PPCsLL-37-Hep) which were then LbL-assembled with positively-charged chitosan (Chi). The multilayer architecture and LL-37 release behavior were expected to vary depending on the assembly strategy, which may in turn affect the obtained antibacterial properties. Here, X-ray photoelectron spectroscopy (XPS) was used to determine the composition of the thin films, i.e., the relative proportions of Hep, Chi, and LL-37 in the multilayers. These proportions were estimated by combining XPS peak analysis with stoichiometric modeling, based on the theoretical degree of protonation of the charged moeities and the use of sulfur as a specific marker for Hep. However, discrepancies between the modeled values and the XPS data revealed that theoretical assumptions could not fully account for the measurements, and modeling was then refined for improved accuracy using empirical protonation degrees. The results show that a higher proportion of LL-37 is retained in the antimicrobial films when using bare LL-37 compared to PPCsLL-37-Hep, likely due to molecular rearrangement following the addition of Chi to the previous PPCsLL-37-Hep layer, which induces partial LL-37 release. The developed methodology, based on in-depth exploitation of XPS data, enables a more advanced characterization of these antimicrobial films and may guide their synthesis and performance optimization.